(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: The study on the status of training in the Indian IT industry with the impact of artificial intelligence adopts a mixed-methods research design. Firstly, a quantitative approach involves collecting data through surveys administered to IT professionals, training providers, and industry stakeholders. The survey will capture information regarding the current training programs, the incorporation of AI-related skills, and the perceived effectiveness of existing training initiatives. Additionally, qualitative methods such as interviews and focus group discussions will be employed to gain deeper insights into the challenges and opportunities associated with AI training in the Indian IT sector. Interviews with key industry players and training experts will provide nuanced perspectives on the effectiveness of AI training programs, while focus group discussions with IT professionals will facilitate discussions on their experiences and needs regarding AI skills development. The integration of quantitative and qualitative data will offer a comprehensive understanding of the status of AI training in the Indian IT industry, enabling the identification of key areas for improvement and the formulation of recommendations to enhance training initiatives and address emerging challenges Design: The research adopted a conceptual approach, utilizing a descriptive research design to explore the status of training in the Indian IT industry and its impact on artificial intelligence. Secondary data was collected and analyzed to uncover the factors influencing the industry. The study aims to equip professionals with the necessary skills to navigate the evolving work environment and effectively tackle diverse challenges. Notably, it reveals that individuals with high IQ levels during their schooling often struggle to excel in their careers due to a deficiency in emotional intelligence (EQ). This insight underscores the importance of integrating EQ training alongside technical skills development in the Indian IT industry to foster well-rounded professionals capable of thriving in AI-driven workplaces. Findings: Findings from studies on the status of training in the Indian IT industry with the impact of artificial intelligence reveal a blend of challenges and opportunities. Despite the increasing emphasis on AI training, hurdles to its widespread adoption persist. These challenges encompass a scarcity of proficient AI trainers, restricted access to AI infrastructure, and the swift pace of technological advancements. However, amidst these challenges, the studies illuminate several avenues for enhancing AI training initiatives. These include fostering collaborative industry-academia partnerships, leveraging government initiatives to promote AI education, and developing specialized certification programs in AI. Looking forward, AI is projected to continue reshaping the training landscape in the Indian IT sector. Organizations prioritizing AI training stand to gain a competitive edge, fostering innovation, heightening productivity, and attracting top talent. Furthermore, ongoing upskilling and reskilling endeavours are deemed vital for adapting to the evolving AI-driven workplace dynamics and ensuring enduring growth and relevance in the global IT market. Originality/value: This study includes a detailed study of the status of training in the Indian IT industry with the impact of artificial intelligence. Paper type: Conceptual Research